Research on Improving the Interviewing of Suspects - Ray, Bull (Magyar Rendészet, 2025)
This publication overviews some of the author’s involvement regarding international developments in recent decades related to the improving of interviews with suspects. Its aim is to demonstrate how research has been informing policies and practices around the world. In light of psychological research, a growing number of countries/organisations have decided to adopt a model/approach of “investigative interviewing” of suspects that does not rely on coercive or oppressive methods. This article will overview 1. the evolution of the ‘PEACE method’; 2. some of the research on the effectiveness of aspects of the ‘PEACE’ method; and 3. the 2021 publication of the ‘Principles of Effective Interviewing’ (drafted at the request of the United Nations). In 2016, the United Nations “Special Rapporteur on torture and other cruel, inhumane or degrading treatments” (law professor Juan Méndez) submitted his report to the United Nations, which stated that “The Special Rapporteur […] advocates the development of a universal protocol identifying a set of standards for non-coercive interviewing methods and procedural safeguards that ought, as a matter of law and policy, to be applied at a minimum to all interviews by law enforcement officials, military and intelligence personnel and other bodies with investigative mandates.” The current publication here demonstrates that police and other investigative agencies can be willing to update/improve their interviewing of suspects by taking note of the findings of relevant research.